Design and Build Online Sales on Website-Based Butiq Bilqis Store Using PHP MySQL - Farhatus Sulaeha; Irma Yunita; Fajriyanto (Universitas Muhammadiyah Palu, 2024)
Butiq Bilqis is one in the Asembagus (The Second City) Situbondo area which offers various types of clothing related needs such as robes from small to adult. Most of the information systems developed do not take into account the resource limitations faced by small and medium businesses. This research aims to overcome this challenge with a simpler and more cost-effective solution. To expand market reach and promote products, the system will be integrated with social media platforms such as Facebook and Instagram, which are widely used by Butiq Bilqis' target market. Testing is carried out to ensure all system features function properly, including product management, ordering, payment and stock management. By adopting this online sales system, Butiq Bilqis can run its operations more easily and efficiently, increase customer satisfaction and achieve better sales growth.